Inhibition of growth, biofilm formation, virulence, and surface attachment of Agrobacterium tumefaciens by cinnamaldehyde derivatives - Ahmed, Bilal; Jailani, Afreen; Lee, Jin-Hyung; Lee, Jintae (Frontiers in Microbiology, 2022)
Agrobacterium tumefaciens, a soil-borne, saprophytic plant pathogen that colonizes plant surfaces and induces tumors in a wide range of dicotyledonous plants by transferring and expressing its T-DNA genes. The limited availabilities and efficacies of current treatments necessitate the exploration of new anti-Agrobacterium agents. We examined the effects of trans-cinnamaldehyde (t-CNMA) and its derivatives on the cell surface hydrophobicity, exopolysaccharide and exo-protease production, swimming motility on agar, and biofilm forming ability of A. tumefaciens. Based on initial biofilm inhibition results and MIC data, 4-nitro, 4-chloro, and 4-fluoro CNMAs were further tested. 4-Nitro, 4-chloro, and 4-fluoro CNMA at ≥150 µg/ml significantly inhibited biofilm formation by 94-99%. Similarly, biofilm formation on polystyrene or nylon was substantially reduced by 4-nitro and 4-chloro CNMAs as determined by optical microscopy and scanning electron microscopy (SEM) and 3-D spectrum plots. 4-nitro and 4-chloro CNMAs induced cell shortening and concentration- and time-dependently reduced cell growth. Virulence factors were significantly and dose-dependently suppressed by 4-nitro and 4-chloro CNMAs (P≤0.05). Gene expressional changes were greater after 4-nitro CNMA than t-CNMA treatment, as determined by qRT-PCR. Furthermore, some genes essential for biofilm formation, motility, and virulence genes significantly downregulated by 4-nitro CNMA. Seed germination of Raphanus sativus was not hindered by 4-nitro or 4-fluoro CNMA at concentrations ≤ 200 µg/ml, but root surface biofilm formation was severely inhibited. This study is the first to report the anti-Agrobacterium biofilm and anti-virulence effects of 4-nitro, 4-chloro, and 4-fluoro CNMAs and t-CNMA and indicates that they should be considered starting points for the development of anti-Agrobacterium agents.